Effect of dietary protein levels in the formulated diets on growth and survival of juvenile spiny lobster Panulirus homarus (Linnaeus) - Muthu Rathinam, Margaret; K. Kizhakudan, Joe; Vijayagopal, P.; Jayasankar, Vidya; Leslie, V. A.; Sundar, R. (Indian Journal of Fisheries, 2014)
Effect of dietary protein level on the growth and survival of juvenile spiny lobster Panulirus homarus was evaluated. Pellet diets containing three different protein levels of 340 g kg-1 (diet A), 400 g kg-1 (diet B) and 460 g kg-1 (diet C), and a control diet of clam meat (diet D) with 470 g kg-1 protein were used. The duration of the experiment was 90 days. Survival was 100% for lobsters fed on diet C, 95% for lobsters fed on diet A, and 85% and 60% respectively for lobsters fed diets B and D. The results indicated that diet C gave the highest growth of 0.088 (± 0.10) mm CL followed by diet B with 0.055 (± 0.12) mm and diet A with 0.044 (± 0.10) mm in comparison to the control diet (diet D) with 0.077 (± 0.12) mm growth per day which indicated that next to clam meat, diet C with 460 g kg-1 protein level gave highest growth. The specific growth rate (SGR) was 0.627 ±0.03, 0.547 ± 0.03 and 0.354 ± 0.01 respectively for the diets C, B and A in comparison to the SGR of the clam diet (diet D) which was 0.685 ± 0.05. Diet C with a protein level of 460 g kg-1 gave good survival, SGR and FCR next to clam meat diet (D).